2001
DOI: 10.2337/diabetes.50.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Decreased In Situ Insulin Receptor Dephosphorylation in Hyperglycemia-Induced Insulin Resistance in Rat Adipocytes

Abstract: The regulation of insulin receptor (IR) tyrosine (tyr) phosphorylation is a key step in the control of insulin signaling. Augmented IR tyr dephosphorylation by protein tyrosine phosphatases (PTPs) may contribute to insulin resistance. To investigate this possibility in hyperglycemia-induced insulin resistance, primary cultured rat adipocytes were rendered insulin-resistant by chronic exposure (18 h) to 15 mmol/l glucose combined with 10 -7 mol/l insulin. Insulin-resistant adipocytes showed a decrease in insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…However, in this model of insulin resistance, we have recently found that IR-related PTP activity is diminished rather than elevated (77). These findings are in agreement with other in vitro (78) and in vivo (79,80) studies demonstrating that hyperglycemiainduced insulin resistance is not associated with increased IR Tyr dephosphorylation or PTP activity.…”
Section: Discussionsupporting
confidence: 80%
“…However, in this model of insulin resistance, we have recently found that IR-related PTP activity is diminished rather than elevated (77). These findings are in agreement with other in vitro (78) and in vivo (79,80) studies demonstrating that hyperglycemiainduced insulin resistance is not associated with increased IR Tyr dephosphorylation or PTP activity.…”
Section: Discussionsupporting
confidence: 80%
“…Isolation of epididymal fat pads. Male Sprague-Dawley rats or male mice were killed, epididymal fat pads were removed, and adipocytes were isolated as described (18). After collagenase digestion, adipocytes were filtered through 20-mesh and washed three times with 3% BSA-Krebs-Ringer bicarbonate HEPES buffer (118 mmol/l NaCl, 5 mmol/l KCl, 1.2 mmol/l MgSO 4 , 2.5 mmol/l CaCl 2 , 1.2 mmol/l KH 2 PO 4 , 5 mmol/l NaHCO 3 , 30 mmol/l HEPES, and 1 mmol/l pyruvate, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Isolated adipocytes were incubated with various concentrations of bradykinin and/or NO inhibitors/scavengers/ donors for the times indicated. Basal and insulin-stimulated (100 nmol/l for 30 min at 37°C) rates of glucose uptake were assayed as described (18). Western blotting.…”
Section: -Deoxy-d-[mentioning
confidence: 99%
“…Normalization of mitochondrial reactive oxygen species by a number of different approaches prevents these phenomena (2). In adipocytes, Tang and colleagues (3) have shown that a combination of hyperglycemia and hyperinsulinemia results in reduced insulin-stimulated glucose uptake that was in part because of reduced insulin receptor dephosphorylation.…”
mentioning
confidence: 99%
“…Measurement of [1][2][3] H]2-Deoxyglucose Uptake-Assay of [ 3 H]2-deoxyglucose uptake was performed as described previously (8). Briefly, the cells were glucose starved for 30 min.…”
mentioning
confidence: 99%